Analisis Tata Kelola Sistem Informasi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bandung Barat - Maulana, Taufiq Arya; Rosmiati, Mia (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The government has changed the way they provide services due to the COVID breakout in 2020. One of the beneficiaries is the West Bandung Region (WBR) Population and Civil Registry Office. However, due to digital data and information processing from technology is a novelty for the agency, there are quite a problem raises from it, namely the reliability of the server which leads to the agency unable to work since everything is processed within the server, the lack of human resources for Information Techonology (IT), and the reliance of old technologies. Therefore, there is a need to assess their capability in governing their Information System. For this, COBIT 2019 framework is used since it can assess the problems. The objectives are EDM04, APO02, APO05, APO07, BAI02, BAI03, BAI05, and DSS01. From the assessment, it was found that they have the capabilites, but are low on resources to fulfill their needs.